Sistem Informasi Penyuluhan Pertanian Berbasis Web pada Dinas Pertanian dan Perkebunan Provinsi Aceh - Zulvi, Audrey Oktia; Muhktar (Jurnal Sistem Komputer (SISKOM), 2025)
This study aims to develop and implement a Web-based Agricultural Extension Information System at the Department of Agriculture and Plantation of Aceh Province. The system is designed to facilitate farmers' access to agricultural information, enhance the effectiveness of agricultural extension services, and support improvements in agricultural productivity and quality. The methods used include literature review, user needs analysis, system design, web application development, and field implementation trials. A participatory approach involves farmers, agricultural extension officers, and other stakeholders to ensure the system meets local needs. The system provides information related to cultivation techniques, market changes, government policies, and weather forecasts, which are expected to help farmers improve production efficiency, reduce risks, and expand market access. The Department of Agriculture and Plantation also benefits from delivering extension services effectively, covering topics such as agricultural business management and marketing. The results of this study are expected to offer significant benefits to farmers and communities, including improved access to information, more effective extension services, and increased agricultural productivity and quality.